ANALYSIS OF TRANSPORTATION MODE CHOICE IN MALANG CITY USING MULTINOMIAL LOGISTICS METHOD - Madu Sonia; Meriana Wahyu Nugroho; Titin Sundari; Rahma Ramadhani (Journal Innovation of Civil Engineering)
In every urban area, especially in the Malang area, modes of transportation are increasingly diverse, ranging from private vehicles, public transportation, to online-based transportation. This research aims to determine the choice of transportation mode using the multinominal logistics method. With this type of quantitative research and data sources through surveys conducted in 5 sub-districts of Malang City using the multinominal logistics method. The research results showed that 11% of respondents went from home to another place for work using private transportation, 3% of respondents were still students. 88% of working respondents and housewives chose public transportation, 97% of whom were still students. 9% of respondents who work and are housewives use online vehicles while 0% are still students.